PENGELOLAAN SPOT LAYANAN DALAM UPAYA PENINGKATAN EKONOMI KREATIF DI DESA WISATA CEPAKA - Komang Krishna Yogantara; Dewiwati Sujadi (Synergy and Society Service, 2021)
Cepaka Village as a partner village of Triatma Mulya University has expressed their desire to form a tourist village, but their limited knowledge of tourism villages becomes an obstacle in making it happen. The focus of this activity is carried out based on the above grouping, namely realizing, packaging / packaging tourism villages by involving all existing potential, and involving village communities, management / governance of SMEs and services that will become the core products of tourism villages and the impact of tourism villages, implementing mentoring activities for community financial institutions in cooperatives, LPDs, traditional markets, waste banks and BUMDES. In accordance with the problems faced by partners in this service activity, the implementer can provide several solutions in accordance with existing conditions in the field. The implementation of community service activities in Cepaka Village includes several activities that have been carried out to increase the number of tours. As for the implementation of the program, namely: Programs in the Environmental Sector that have been implemented in Cepaka Village, including Community Service in the Cepaka Harum Plastic Bank area.